PROMOTING MORAL MESSAGES BEHIND FIGURATIVE LANGUAGES IN NIRWANA’S SONG LYRICS - Hamzah Fikri Mashobi; Rismiyanto - Rismiyanto; Mutohhar - Mutohhar (Universitas Muria Kudus, 2022)
Figurative Language is commonly used in literary work, especially in a song lyric. The song is also commonly used by English teachers as a medium in the teaching process. It makes the learning proses becomes more interesting and satisfying. Besides that, the song also contains a moral message which is implied in the lyrics which can be used by the teachers to teach the students in building the characters. This research is aimed at finding the types and meaning of the figurative language which are used in Nirvana’s song lyrics and to explain the interpretation of the meanings which support moral message. This research is descriptive qualitative research. The data of this research are the words, phrases, and sentences of Nirvana songs that use figurative language. The data source is taken from all of Nirvana's song lyrics in the “Nevermind” Album. The result of the research indicates that the there are 13 types of figurative language, those are Metaphor (32,7%), Symbolism (30,2%), Idiom (9,5%), Hyperbole (5,2%), Metonymy (3,4%), Satire (3,4%), Synecdoche (2,6%), Pun or Paronomasia (2,6%), (2,6%), Litotes (2,6%), Paradox (2,6%), Simile (1,7%), and Personification (0,9%); and that the most moral messages delivered in Nevermind Album are bravery and honesty.